SUPER-CAPACITOR APPLICATION IN ELECTRICAL POWER CABLE TESTING FACILITIES IN THERMAL ENDURANCE AND MECHANICAL BRACING TESTS - I. V. Oleksyuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The current-carrying cores of the electrical power cables should be resistant to effects of short-circuit currents whose values depend on the material of the core, its cross-sectional area, cable insulation properties, environment temperature, and the duration of the short-circuit current flow (1 and 3–4 sec. when tested for thermal endurance and mechanical bracing). The facilities for testing the 10 kV aluminum core cables with short-circuit current shall provide mechanical-bracing current 56,82 kA and thermal endurance current 11,16 kA. Although capacitors provide such values of the testing currents to the best advantage, utilizing conventional capacitor-units will involve large expenditures for erecting and  running a separate building. It is expedient to apply super-capacitors qua the electric power supply for testing facilities, as they are capacitors with double-electrical layer and involve the current values of tens of kilo-amperes.The insulation voltage during short-circuit current testing being not-standardized, it is not banned to apply voltages less than 10 kV when performing short-circuit thermal endurance and mechanical bracing tests for electrical power cables of 10 kV. The super-capacitor voltage variation-in-time graph consists of two regions: capacitive and resistive. The capacitive part corresponds to the voltage change consequent on the energy change in the super-capacitors. The resistive part shows the voltage variation due to the active resistance presence in the super-capacitor.The author offers the algorithm determining the number of super capacitors requisite for testing 10 kV-electrical power cables with short-circuit currents for thermal endurance and mechanical bracing. The paper shows that installation of super-capacitors in the facilities testing the cables with short-circuit currents reduces the area needed for the super-capacitors in comparison with conventional capacitors more than by one order of magnitude.